m6A Regulators Mediated Methylation Modification Patterns and Tumor Microenvironment Infiltration Characterization In Nasopharyngeal Carcinoma - Liu, Zijian; He, Jinlan; Han, Jiaqi; Yang, Jiangping; Liao, Wenjun; Chen, Nianyong (Frontiers in Immunology, 2022)
Background The role of RNA N6-methyladenosine (m6A) modification in tumor progression and metastasis has been demonstrated. Nonetheless, potential biological function of m6A modification patterns in nasopharyngeal carcinoma (NPC) remains unknown. Methods The m6A modification patterns were comprehensively evaluated based on 26 m6A regulators in NPC, and m6A subtype and also m6A score were identified and systematically correlated with representative tumor characteristics. Results Two distinct m6A subtypes were determined and were highly consistent with immune activated and immune suppressed phenotypes, respectively. More representative m6A scores of individual tumors could predict tumor microenvironment (TME) infiltration, mRNA based stemness index (mRNAsi), EBV gene expression, genetic variation, and prognosis of NPC patients. Low m6A score, characterized by activation of immunity and suppression of mRNAsi and EBV gene, indicated an activated TME phenotype and better PFS and also lower risk of recurrence and metastasis. High m6A score, characterized by activation of Wnt and NF-κB signaling pathway and lack of effective immune infiltration, indicated an immune suppressed TME phenotype and poorer survival. Low m6A score was also correlated with increased tumor mutation burden (TMB) and better response to immunotherapy, and vice versa. A significant therapeutic advantage in patients with low m6A score was confirmed with an anti-PDL1 immunotherapy cohort. Conclusions m6A patterns played an important role in the diversity and complexity of TME. m6A score could be used to evaluate the m6A pattern of individual tumor to enhance our understanding of TME infiltration and guide more effective immunotherapy strategies.